2010
DOI: 10.1111/j.1471-4159.2010.06937.x
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β and LPS modulate ADP‐induced migration of microglial cells through P2Y1 and P2Y12 receptor expression

Abstract: J. Neurochem. (2010) 115, 450–459. Abstract Nucleotides act as early signals for microglial recruitment to sites of CNS injury. As microglial motility and activation can be influenced by several local factors at the site of the lesion, we investigated the effects of interferon‐gamma, lipopolysaccharide (LPS) or transforming growth factor‐β (TGF‐β) addition to mixed glial cell cultures, on microglial migration in response to ADP, P2Y12 and P2Y1 mRNA expression as well as on the expression of an array of genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 44 publications
8
80
1
Order By: Relevance
“…In addition, in vitro studies have also confirmed P2Y 1 R expression in microglia (Ballerini et al, 2005;De Simone et al, 2010). However, in this report, we have shown that the P2Y 1 R is expressed on astrocytes before and after focal cerebral ischemia, using an in vivo model.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, in vitro studies have also confirmed P2Y 1 R expression in microglia (Ballerini et al, 2005;De Simone et al, 2010). However, in this report, we have shown that the P2Y 1 R is expressed on astrocytes before and after focal cerebral ischemia, using an in vivo model.…”
Section: Discussionmentioning
confidence: 48%
“…2a). These results suggest that ADPβS activates microglia P2Y 1,12 and/or P2Y 13 receptors, which induce the release of diffusible messengers that attenuate its proliferative effect in astrocytes. They further suggest that the co-presence of astrocytes and microglia, and eventually their physical contact, facilitates the release of these inhibitory messengers since CCCM-S, but not MCM-S, attenuated ADPβS proliferative effect ( Table 2).…”
Section: Microglia Soluble Factors and Cell Deathmentioning
confidence: 83%
“…Therefore, besides the inhibitory influence provided by the presence of microglia, activation of microglia P2Y receptors sensitive to ADPβS seem to contribute to the release of messengers that interfere with the proliferative effects mediated by astroglial P2Y receptors. Microglia express P2Y 1 , P2Y 12 and P2Y 13 receptors [34,35], which are activated by ADPβS and may regulate the release of messengers, such as interleukin-10 [46]. These messengers may regulate astroglial proliferation mediated by P2Y receptors through a functional interaction occurring at the receptor level and/or at the intracellular signal transduction pathways.…”
Section: Methyl-[mentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of P2Y 12 and P2Y 1 receptors of resting microglia causes their migration along a concentration gradient of ATP/ADP towards the injury. Phagocytosis of injured cells is induced by P2Y 6 receptors activated by UTP/UDP [46][47][48]. Considering this model, P2Y receptors became a pharmacological target for neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%